Non-invasive in vivo determination of viable islet graft volume by 111In-exendin-3 - Wael A. Eter (Nature Portfolio, 2017)
Abstract Pancreatic islet transplantation is a promising therapy for patients with type 1 diabetes. However, the duration of long-term graft survival is limited due to inflammatory as well as non-inflammatory processes and routine clinical tests are not suitable to monitor islet survival. 111In-exendin-SPECT (single photon emission computed tomography) is a promising method to non-invasively image islets after transplantation and has the potential to help improve the clinical outcome. Whether 111In-exendin-SPECT allows detecting small differences in beta-cell mass (BCM) and measuring the actual volume of islets that were successfully engrafted has yet to be demonstrated. Here, we evaluated the performance of 111In-exendin-SPECT using an intramuscular islet transplantation model in C3H mice. In vivo imaging of animals transplanted with 50, 100, 200, 400 and 800 islets revealed an excellent linear correlation between SPECT quantification of 111In-exendin uptake and insulin-positive area of islet transplants, demonstrating that 111In-exendin-SPECT specifically and accurately measures BCM. The high sensitivity of the method allowed measuring small differences in graft volumes, including grafts that contained less than 50 islets. The presented method is reliable, convenient and holds great potential for non-invasive monitoring of BCM after islet transplantation in humans.